Evaluation of carotid artery atheromatous plaques using digital panoramic radiographs with Doppler sonography as the ground truth - Neha Khambete; Rahul Kumar; Mukund Risbud; Anil Joshi (Elsevier, 2012)
Objectives: The objective of the study was to determine whether digital panoramic radiography is a reliable method to detect calcified carotid artery atheromatous plaques (CCAAP) as compared to ultrasonography. Study design: Digital panoramic radiographs were obtained from 50 patients who also underwent carotid ultrasound examination. The images were interpreted by trained maxillofacial radiologist for the presence or absence of calcified atheromatous plaques. The extent of carotid calcification on carotid ultrasonography was determined by a trained sonologist which was considered as gold standard assessment. Results: Digital panoramic radiographs had sensitivity of 76% and specificity of 98.66% in determining calcified carotid artery atheromatous plaques. There was a high level of agreement between diagnoses, with a kappa value of 0.8. Conclusion: To conclude, digital panoramic radiographs had good sensitivity and high specificity in detecting calcified carotid artery atheromatous plaques. If properly trained, dentists can detect such plaques and can refer patients to physician for timely medical treatment.